Coronavirus Disease 2019 in Pregnancy and Outcomes Among Pregnant Women and Neonates: A Literature Review. Issue 5 (12th April 2021) - Mark, Elyse G.; McAleese, Samuel; Golden, W. Christopher; Gilmore, Maureen M.; Sick-Samuels, Anna; Curless, Melanie S.; Nogee, Lawrence M.; Milstone, Aaron M.; Johnson, Julia
Abstract : Supplemental Digital Content is available in the text. Abstract : Limited data are available about the outcomes of coronavirus disease 2019 (COVID-19) during pregnancy and risk of vertical transmission in exposed neonates. We reviewed studies published February 1, 2020, through August 15, 2020, on outcomes in pregnant women with COVID-19 and neonates with perinatal exposure. Among pregnant women with COVID-19, 181 (11%) required intensive care unit admission and 123 (8%) required mechanical ventilation. There were 22 maternal deaths. Most infections occurred in the third trimester. Among women who delivered, 28% had a preterm birth, and 57% had a Caesarean section. Sixty-one (4%) of 1222 neonates with reported testing had at least 1 positive severe acute respiratory syndrome coronavirus 2 polymerase chain reaction test. The most common symptom among neonates was respiratory distress (n = 126; 21%). There were 14 neonatal deaths, one of which occurred in a neonate with positive testing. Further study of COVID-19 in pregnant women and neonates, including standardized reporting of outcomes, testing and treatment protocols, is essential to optimize maternal and neonatal care.